2021
DOI: 10.1210/jendso/bvab017
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Serum Cortisol with Cardiovascular Risk and Mortality in Patients Referred to Coronary Angiography

Abstract: Context Serum cortisol may be associated with cardiovascular risk factors and mortality in patients undergoing coronary angiography, but previous data on this topic are limited and controversial. Objective We evaluated whether morning serum cortisol is associated with cardiovascular risk factors, lymphocyte subtypes and mortality. Design and Setting This is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
4
0
2
Order By: Relevance
“…Almost all smaller crosssectional studies 23,24 have found that patients with AMI had elevated cortisol levels, which increase the risk of fatality and morbidity. Additionally, 25,26 showed a correlation between incident cardiovascular disease (CVD) and plasma cortisol, and such results imply that higher morning cortisol is a causative risk factor for CVD.…”
Section: Resultsmentioning
confidence: 99%
“…Almost all smaller crosssectional studies 23,24 have found that patients with AMI had elevated cortisol levels, which increase the risk of fatality and morbidity. Additionally, 25,26 showed a correlation between incident cardiovascular disease (CVD) and plasma cortisol, and such results imply that higher morning cortisol is a causative risk factor for CVD.…”
Section: Resultsmentioning
confidence: 99%
“…However, steroidogenic capacity in these individuals has not been assessed. Given the association between higher serum cortisol concentrations and cardiovascular risk profile ( 61 ), it would be of interest to assess basal and stimulated glucocorticoid levels in individuals carrying these alleles, which might explain interindividual variability in basal cortisol or physiological cortisol responses, and excess cortisol levels in individuals carrying risk alleles.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there have been numerous reports of cortisol associating with CVD and CVD risk factors. In a prospective cohort study performed at a tertiary care center with 3052 participants who underwent coronary angiography, increased morning serum cortisol was associated with adverse cardiovascular risk factors including elevated systolic blood pressure, higher fasting glucose, increased triglycerides, and lower glomerular filtration rate [ 59 ]. In this study, increased cortisol also associated with higher counts of CD16+CD56+ (NK cells) and CD3+CD8+ (T-suppressor) cells.…”
Section: Biomarkers Of Stress and The Biology Of Adversitymentioning
confidence: 99%